KONTRIBUSI PENGETAHUAN ASBABUNNUZUL DALAM PENGEMBANGAN MATERI AL-QURAN DAN HADITS DI MADRASAH ALIYAH - Natsir, Ahmad; Fahrudin, Ahmad; Wahyudin, Didin; Setiawan, Bagus Wahyu; Werdiningsih, Wilis (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
This article aims to reveal the role of Asbabunnuzul's knowledge on learning lessons in an Islamic school. This knowledge of asbabunnuzul was increasingly emphasized after the public discovery of subject matter which allegedly contained elements of a call to action on radicalism. Finally, at the end of 2019, the Ministry of Religion decided to overhaul the entire syllabus of PAI (Education of Islamic Religion) and Arabic learning materials from the MI (Islamic Elementary School) to the Madrasah Aliyah. Knowledge of asbabunnuzul a verse will make the Koran and the Prophet's hadiths have a relevant interpretation of their time as well as being able to capture divine messages in response to developments in social problems that exist in the contemporary era. It is from here that the material of the Qur'an hadith in Madrasah Aliyah and Tsanawiyah can develop not only to adhere to classical exegesion but to a more dynamic direction and to respond to the times.